Synergy of cAMP and calcium signaling pathways in CFTR regulation - Bozoky, Zoltan (Proc Natl Acad Sci U S A, 2017)
Cystic fibrosis results from mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel, leading to defective apical chloride transport. Patients also experience overactivation of inflammatory processes, including increased calcium signaling. Many investigations have described indirect effects of calcium signaling on CFTR or other calcium-activated chloride channels; here, we investigate the direct response of CFTR to calmodulin-mediated calcium signaling. We characterize an interaction between the regulatory region of CFTR and calmodulin, the major calcium signaling molecule, and report protein kinase A (PKA)-independent CFTR activation by calmodulin. We describe the competition between calmodulin binding and PKA phosphorylation and the differential effects of this competition for wild-type CFTR and the major F508del mutant, hinting at potential therapeutic strategies. Evidence of CFTR binding to isolated calmodulin domains/lobes suggests a mechanism for the role of CFTR as a molecular hub. Together, these data provide insights into how loss of active CFTR at the membrane can have additional consequences besides impaired chloride transport.